Analisis Dampak Turbulensi Di Era Globalisasi Pada Pendidikan Islam Di Indonesia - Munawir, Munawir; Putri, Meria Sindy Amanda; Rofif, Dimas Fayruz (LP2M Universitas Islam Ahmad Dahlan, 2024)
This research is motivated by the erosion of the morals of the nation's children which began to lead to negative things. The purpose of this research is to be a way and source of opening their minds about the turbulence of global currents embedded in them. The method used is library research by obtaining and collecting data through existing literature sources. The results and discussion in this research are that Islamic education is always reflected in noble morals and also upholds good manners, in this era of globalization there are turbulences (shocks) that lead to negativity. Which is discussed with sub-chapters discussing the turbulence of education in the era of globalization, the influence, and challenges of globalization in the world of education, the positive impact of globalization on the world of Indonesian education (multimedia interactive teaching), the negative impact of globalization on the world of Indonesian education, Islamic education and the era of globalization, and solutions to Islamic education in the era of globalization. It can be concluded that with the turbulence in the current era of globalization, Islamic education can take a stand in the middle, not anti-global, but also not dragged into the bad currents of globalization, maintaining Islamic values.